Working Relations of the Village Head and the Village Consultative Body in the Village Funds Utilization - Muhammad Mukaddar; M Chairul Basrun Umanailo; Darwin Abd Radjak; Andries Lionardo; Nanik Handayani (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This study aims to identify the relationship between the village head and the Village Consultative Body (BPD) in the use of village funds in the village of Karang Jaya, Namlea District, and explain the influence on the development of village communities. The problem is focused on the use of village funds which should be a stimulus for development in each village, but, in management, there are often problems that hinder village development. This study seeks to see and get deeper into the relationship that has been built between the village head and the BPD in the village of Karang Jaya. The approach used in this study uses a qualitative approach. The number of informants who will be interviewed is 15 people taken purposively, considering that respondents are regarded as related parties to achieve the research objectives. Researchers used observational data collection techniques and in-depth interviews to obtain data on the implementation of the village fund program. The analysis technique used in this research is qualitative data analysis following the concepts given by Miles and Huberman, and Spradley. This study concludes that the parallel relationship pattern between the BPD and the village head in the management of the village government as regulated in the legislation, it turns out that in its implementation, there is enough response so that the working relationship becomes harmonious and leads to a pattern of cooperation and shows a tendency to share tasks that are parallel between the heads. Villages and BPD in the use of village funds.